Hand cleaning activities during COVID-19 pandemic and the manifestation on human skin: a retrospective study - Ummu Mastna Zuhri; Wicaksono, Arko Jatmiko (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2020)
Hand sanitizing is a popular hand-cleaning technique during the pandemic.In the present article, a retrospective study by observational and quantitative data analysis involving 155 respondents were collected through questionnaires. The most intense methods of hand-cleaningactivities (i.e. hand sanitizing, hand washing with soap, alcohol rubs, wet wipes, dried wipes and hand washing with water only)were investigated. Manifestation on human skin was evaluated personally by take into account to the real condition of the authors. Validity of the retrospective questionnaire was assessed by comparing it to the prospective journal which was considered as the reference method. As the result, hand-washing with soap is the most preferred hand-cleaning method during pandemic (94 %, total sample population n = 155). Adverse event by the usage of alcohol might observed especially during the first 4 months of the pandemic period.